Post a New Question

Algebra

posted by .

solve equations by elimination

2x-6y=3 (1)
4x+9y=-1 (2)

  • Algebra -

    Multiply first equation with -2

    - 4 x + 12 y = -6

    Note that, if you add down, the y's will cancel out.

    - 4 x + 12 y = - 6

    4 x + 9 y = - 1

    ( - 4 x + 4 x ) + ( 12 y + 9 y ) = -6 + ( -1 )

    0 + 21 y = -6 - 1

    21 y = - 7 Diwide both sides with 21

    y = - 7 / 21

    ( Remark: 7 / 21 = 1 / 3 )


    y= - 1 / 3


    First equation:

    2 x - 6 y = 3

    2 x - 6 * ( - 1 / 3 ) = 3

    2 x + 6 / 3 = 3

    2 x + 2 = 3

    2 x = 3 - 2

    2 x = 1 Divide both sides with 2

    x = 1 / 2


    x = 1 / 2 , y= - 1 / 3

  • Algebra -

    Thank You

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question